A CHANGING DISCOURSE ONTHE RED CROSS SOCIETY OF CHINA BEYOND CIVIL SOCIETY - Wei, Bingling (PEOPLE: International Journal of Social Sciences, 2015)
This paper explores non-government organizations (NGOs) in the People’s Republic of China, where the Communist Party of China (CCP) has extensive influence over society and Western notions of NGOs operating in civil society must be reconceptualised. To analyze this unique situation, this paper examines the Red Cross Society of China (RCSC), a member of the International Federation of Red Cross and Red Crescent Societies (IFRC) and its distinct role in China. It also discusses how the RCSC provides a general example of how NGOs operate within a Party-State environment. This research is significant as it goes beyond the services the Red Cross Society of China provides to citizens and places these services within Western theories on the public sphere and civil society. The theoretical analysis is to support its perspective on public spheres and civil society and explore the changes of the Red Cross Society of China in the changing political climate of China.